An 40Ar-39Ar investigation of the Mertz Glacier area (George V Land, Antarctica): implications for the Ross Orogen - East Antarctic Craton relationship and Gondwana reconstructions - DI VINCENZO, G.; TALARICO, F. M.; KLEINSCHMIDT, G. (Precambrian Research, 2007)
George V Land (Antarctica) includes the boundary between Late Archean–Paleoproterozoic metamorphic terrains of the East Antarctic craton and the intrusive and metasedimentary rocks of the Early Paleozoic Ross–Delamerian Orogen. This therefore represents a key region for understanding the tectono-metamorphic evolution of the East Antarctic Craton and the Ross Orogen and for defining their structural relationship in East Antarctica, with potential implications for Gondwana reconstructions. In the East Antarctic Craton the outcrops closest to the Ross orogenic belt form the Mertz Shear Zone, a prominent ductile shear zone up to 5 km wide. Its deformation fabric includes a series of progressive, overprinting shear structures developed under different metamorphic conditions: from an early medium-P granulite-facies metamorphism, through amphibolite-facies to late greenschistfacies conditions. 40Ar–39Ar laserprobe data on biotite in mylonitic rocks from the Mertz Shear Zone indicate that the minimum age for ductile deformation under greenschist-facies conditions is 1502±9 Ma and reveal no evidence of reactivation processes linked to the Ross Orogeny. 40Ar–39Ar laserprobe data on amphibole, although plagued by excess argon, suggest the presence of a ∼1.7 Ga old phase of regional-scale retrogression under amphibolite-facies conditions. Results support the correlation between the East Antarctic Craton in the Mertz Glacier area and the Sleaford Complex of the Gawler Craton in southern Australia, and suggest that the Mertz Shear Zone may be considered a correlative of the Kalinjala Shear Zone. An erratic immature metasandstone collected east of Ninnis Glacier (∼180 km east of the Mertz Glacier) and petrographically similar to metasedimentary rocks enclosed as xenoliths in Cambro–Ordovician granites cropping out along the western side of Ninnis Glacier, yielded detrital white-mica 40Ar–39Ar ages from ∼530 to 640 Ma and a minimum age of 518±5 Ma. This pattern compares remarkably well with those previously obtained for the ...